The presence of vessels encapsulating tumor clusters is associated with an immunosuppressive tumor microenvironment in hepatocellular carcinoma. Issue 12 (2nd September 2022) - Zhang, Peiyi; Ono, Atsushi; Fujii, Yasutoshi; Hayes, Clair Nelson; Tamura, Yosuke; Miura, Ryoichi; Shirane, Yuki; Nakahara, Hikaru; Yamauchi, Masami; Uchikawa, Shinsuke; Uchida, Takuro; Teraoka, Yuji; et al.
Abstract: Recently, a distinct vascular pattern in hepatocellular carcinoma (HCC) called vessels encapsulating tumor‐forming clusters (VETC) has received attention because of its association with poor prognosis. However, little is known about the mechanism by which VETC promotes an aggressive phenotype at the molecular level. In our study, the association between differences in stepwise signal intensity in the HB phase and molecular subtypes and somatic mutations associated with the immune microenvironment were investigated using the International Cancer Genome Consortium (ICGC) cohort (66 patients). To our knowledge, this is the first study to analyze the molecular patterns of VETC using RNA‐Seq data. The VETC+ HCC group showed significantly lower overall survival and higher cumulative incidence of extrahepatic metastasis after curative hepatic resection than the VETC− HCC group. The VETC+ group exhibited molecular features indicative of lower immune activation than the VETC− group, suggesting that tumor cells in the VETC+ group were more likely to escape from the immune response, which could lead to the shorter OS (Overall survival) and higher risk of metastasis. On the other hand, gene expression levels of fibroblast growth factor receptors were upregulated in VETC+ HCC, suggesting that VETC+ HCC might benefit from lenvatinib treatment. Our results demonstrate that VETC+ HCC was associated with the suppression of tumor immune responses at the molecular level. Abstract : What's new? A distinct vascular pattern is sometimes found in hepatocellular cancer (HCC), called vessels encapsulating tumor‐forming clusters (VETC). VETC is associated with increased rates of metastasis and recurrence, but it is not clear why. Here, the authors investigated the molecular features of HCC with VETC using whole genome sequencing as well as RNA sequencing. They found that cancers with VETC showed indicators of reduced immune activation compared to the non‐VETC tumors. Additionally, the VETC+ cancers expressed more fibroblast growth factor receptor, suggesting that the kinase inhibitor lenvatinib might be useful in treating these cancers.